Pengaruh Penanaman Modal Dalam Negeri, Tenaga Kerja, Ekspor Dan Pengeluaran Pemerintah Terhadap Pertumbuhan Ekonomi Di Indonesia - Fitri Ani Lubis; Nurjannah Nurjannah; Salman Salman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The aim of this research is to determine the influence of Domestic Investment, Labor, Exports and Government Expenditures on Economic Growth in Indonesia. This research explains the influence of Domestic Investment (X1), Labor (X2), Exports (X3), and Government Expenditures (X4) on Economic Growth (Y) in Indonesia. The data used is time series data and was obtained from the Indonesian Central Bureau of Statistics (BPS) for 2006-2020. The data analysis method uses multiple linear regression analysis using eviews 10 software. The research results show that partially domestic investment has a positive and significant effect on economic growth in Indonesia. Partially, labor has a positive and insignificant effect on economic growth in Indonesia. Simultaneously domestic investment, labor, exports and government spending have a positive and significant effect on economic growth in Indonesia.